Advance Organizer Learning Model to Improve Critical Thinking Skills - Ahmad Yani; Rama A. Mochsen; Charles Steven Karmaley (Postgraduate, University of Mataram, 2023)
This classroom action research aims to improve students' critical thinking skills in class V at UPTD SDI Osmok Kupang for the 2022/2023 academic year through the application of the Advance Organizer learning model. The subjects of this research were 16 students class V of UPTD SDI Osmok Kupang. Data collection techniques use tests and observations. The results of this research show that the percentage of cycle I teacher activity at meetings I and II was 58.75% and the activity of cycle I students at meetings I and II was 55,00%. In cycle II, teacher activity at meetings I and II increased with a percentage of 98.12% and for students in cycle II meetings I and II with a percentage of 96.90%. Apart from that, the results of the critical thinking ability test of students from cycle I to cycle II also increased with the percentage of posttests completed in the cycle, namely 37.50% with an average of 53.43% and in cycle II with a percentage of 93.75% with an average of an average of 86.25% completed in the very good category.